An analysis of Soviet views on John Maynard Keynes - Turner, Carl B. (Durham, N.C. : Duke University Press, 1969)
The purpose of this study is to analyze the Soviet criticism of John Maynard Keynes and his major works from the founding of the Soviet state in 1917 to the retirement of Khrushchev in October, 1964.
Includes index.
Includes bibliographical references: p. 167-179.
rpm 02/11/2017
Loans
Keywords: Keynes, John Maynard; Keynesian economics